Metode Diferensiasi IMPLEMENTASI METODE DIFERENSIASI DALAM PEMBELAJARAN SOR SINGGIH BASA BALI PADA SISWA KELAS VIII SMP NEGERI 3 ABIANSEMAL - Sayu Putu Ratih; Ni Wayan Arini; A.A Diah Indrayani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The lack of interest of students in using Balinese language in daily life is because the learning method used is not appropriate to attract students' attention to enjoy learning Balinese. So the teacher tries to improve students' understanding and skills in communicating using Balinese language with the differentiation method. The differentiation method is one method that uses learning media during learning activities and involves students in using individual learning methods in understanding Balinese language material. The problems studied are, 1) How is the implementation of the differentiation method in learning Balinese language sor singgih by class VIII students of SMP Negeri 3 Abiansemal?, 2). What problems are felt and what efforts are made by teachers and class VIII students of SMP Negeri 3 Abiansemal in learning Balinese language sor singgih using the differentiation method?, 3) What impacts are felt by class VIII students of SMP Negeri 3 Abiansemal when learning Balinese language sor singgih using the differentiation method? The theories used in this study include: Behaviorism Theory and Constructivism Theory. The research method used is qualitative. Data sources obtained through observation, interviews, documentation and literature. The resource persons were the principal of SMP Negeri 3 Abiansemal, the Balinese language teacher for class VIII and students of class VIII of SMP Negeri 3 Abiansemal. The results of the study after using the differentiation method in learning Sor Singgih Basa Bali applied to class VIII A students of SMP Negeri 3 Abiansemal were: 1) Improving speaking skills, 2) Improving students' motivation and interest, 3). Improving students' creativity and self-confidence.